Assessment and recommendation to improve route planning in the Philippines - Casilisilihan, John Mark P.; Suarez, Joshua Philip C.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Transportation helps shape an area's economic health and quality of life. An efficient public transport network must be able to achieve this. For years, the Department of Transportation (DOTr) has made efforts to improve the public transport route planning process in the country. In June 2017, DOTr issued DO No. 2017-011 or simply known as the Omnibus Franchising Guidelines which empowers the local government units to design, plan, and implement their own public transport route network using the Local Public Transport Route Plan (LPTRP) Manual. However, the guideline still recommends the use of the Route Measured Capacity (RMC) in the supply-demand analysis which has been argued to have issues when used in determining supply (Mendoza, et. al (2008), Manresa, et. al). To address this, analysis and comparison of local and foreign provisions are done to provide recommendations for the improvement of the existing public route planning methods in the country. Incorporating a Comfortability Factor in the calculation of the Load Factor accounts for the level of service the passengers experience while still securing a profit for the operators and drivers. Standard headways for jeepneys, buses, and UV express during peak and off peak hours are also recommended depending on the vehicle's service characteristics to protect passengers from excessive waiting. The case study in the Cubao-Divisoria jeepney route concludes that the recommendations achieved its goals - meet the demand and secure balance between comfortability and profitability.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- Planning. -- Philippines; Route surveying